Analisa Pengujian Kekerasan pada Cakram Rem Motor Yamaha Sport (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Brake discs are one of the motorcycle spare parts that function to connect and reduce speed when the motorbike is moving, although very simple, this spare part is part of the braking system and has a very important role, without braking it will endanger the driver and other road users. To determine the hardness of the motorcycle brake disc on two original brake discs and variation brake discs on the Yamaha Vision sport motorbike by conducting Rockwell hardness tests on the original and variation brake discs with 10 test variable points. The results obtained for the average value at the level of hardness on the original disc sample are 55.1 HRC and the average value on the variation disc sample is 44.6 HRC, and the conversion hardness value from the Rockwell test. For Brinell testing and tensile testing from the results of Rockwell hardness testing, the average Brinell and tensile test values ​​were converted from the test site with the average Brinell conversion results for the original disc being 575 HBS, while the average variation disc value was 417.1 HBS, the conversion tensile test value with the results on the original disc was 1626 N/mm² and the variation disc was 1427 N/mm² with 10 variable point Rockwell testing and the conversion value of the Brinell hardness test and the original disc tensile test value was still greater than the variation disc tensile test value.